2016
DOI: 10.2214/ajr.16.16056
|View full text |Cite
|
Sign up to set email alerts
|

Accessory Anterolateral Talar Facet in Populations With and Without Symptoms: Prevalence and Relevant Associated Ankle MRI Findings

Abstract: The higher prevalence of the MRI finding of an accessory anterolateral talar facet in ankles with and without symptoms is not statistically significant. This facet may be associated with subjacent talar bone marrow edema-like change on MR images of individuals with and those without symptoms and with sinus tarsi fat obliteration in individuals with symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 11 publications
2
15
2
Order By: Relevance
“…This study has also demonstrated that a large AALTF is found in 2.5% of the specimens [5]. A recent MRI study has found that AALTF is present in 32.7% of patients who have ankle symptoms and in 26% of asymptomatic volunteers [8]. AALTF can be symptomatic and has become increasingly recognized as a source of talocalcaneal impingement [5,9,10].…”
supporting
confidence: 51%
See 2 more Smart Citations
“…This study has also demonstrated that a large AALTF is found in 2.5% of the specimens [5]. A recent MRI study has found that AALTF is present in 32.7% of patients who have ankle symptoms and in 26% of asymptomatic volunteers [8]. AALTF can be symptomatic and has become increasingly recognized as a source of talocalcaneal impingement [5,9,10].…”
supporting
confidence: 51%
“…Peroneal spasm or contracture may also be noted with passive inversion [9]. MRI and CT were used to identify the accessory anterolateral talar facet in several clinical studies [6][7][8]. Bone marrow edema at the talar or calcaneal side as well as sinus tarsi fat edema is significantly more prevalent in symptomatic patients with AALTF [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is appropriate to mention the accessory anterolateral talar facet which articulates with the calcaneus and which also has clinical implications. Aydıngöz et al [ 20 ] in their MRI study found this variation was present in 32.7% of patients with ankle pain and in 26% of volunteers without it. Accessory anterolateral talar facet may contribute to painful talocalcaneal impingement in persons with pes planus [ 20 ].…”
Section: Discussionmentioning
confidence: 93%
“…MRI demonstrated abutting bone marrow edema between the talus and calcaneus. [3][4][5][6]15 This was localized to AALTF and the adjacent calcaneus anterior to the posterior facet. CT scans and MRI were useful for diagnosis in the current case.…”
Section: Discussionmentioning
confidence: 99%